ANALISIS KINERJA RANTAI PASOK PADA PROSES SOURCE, TRANSFORM, DAN FULFILL DENGAN METODE SCOR DAN AHP PADA TELKOM WITEL BANDUNG - Selvi Cahyani; Suryanto Suryanto; Rivani (JURNAL LENTERA BISNIS, 2024)
Telkom Witel Bandung is a telecommunications and networking service provider serving the Telkom Bandung area. The company has experienced staff reductions and organizational changes following the transformation to B2B services, which have impacted the execution of High Speed Internet (HSI) projects. Performance measurement of the supply chain was conducted using the Supply Chain Operation Reference (SCOR) and Analytical Hierarchy Process (AHP) methods. The evaluation focused on three core processes: source, transform, and fulfill. Performance indicators were derived from KPI validation by employees and managers at Telkom Witel Bandung, resulting in 26 selected indicators with attributes including reliability, responsiveness, agility, cost, profit, and environmental. Indicator weighting was performed using AHP with Expert Choice 11. Analysis of normalized actual data revealed that five indicators with scores below 90 (Excellent) require improvement. The total performance score of 117.461 indicates that Telkom Witel Bandung’s performance is classified as very good.